Pengaruh literasi keuangan, perilaku keuangan, dan improvisasi terhadap kinerja UMKM dengan mediasi penggunaan fintek di Kabupaten Jepara - Nimas Aulia Pambajeng Miftahunnajah; Lyna Latifah; Ida Nur Aeni (Universitas Negeri Surabaya, 2026)
This study aims to analyze the influence of financial literacy, financial behavior, and improvisation on the performance of Micro, Small, and Medium Enterprises (MSMEs) through the mediation of fintech use in furniture craftsmen MSMEs in Jepara Regency. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis techniques, data were collected through questionnaires from MSME actors who met certain criteria. The results show that financial literacy has a positive and significant effect on MSME performance, both directly and indirectly through the use of fintech. The use of fintech is proven to be a mediator that strengthens the relationship between financial literacy and MSME performance. However, financial behavior and improvisation do not show a significant effect on performance, either directly or through fintech. These findings emphasize the importance of improving financial literacy and financial technology assistance in encouraging sustainable MSME performance, especially in the craft-based creative economy sector.